Analisis pengendalian dan pengelolaan kas kecil dalam efisiensi penggunaan dana konsumsi rapat di Perusahaan Geothermal Energy - Putri, Alfiyyah Deka; Wijayanti, Rini (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This research aims to determine the analysis of control and management of petty cash in the efficient use of meeting consumption funds in Geothermal Energy Companies. This research uses a qualitative descriptive method. The techniques used in collecting data in this research include observation, interviews and documentation directly with the Geothermal Energy Company. The results of this research show that control and management in Efficiency is not running well. Based on the results of observations and interviews with 20 sources, Control and Management in Efficient Use of Meeting Consumption Funds is still very low seen from the level of overbudget use of petty cash.